Pengaruh Media Google Earth Terhadap Hasil Belajar Siswa Materi Mitigasi Bencana Alam Bermodelkan Group Investigation - Alfansyah, Andreawan; Insani, Nailul (Jayapangus Press, 2024)
Improving the quality of education cannot be separated from learning activities because education includes the learning process. However, in reality, learning that occurs in the school environment is still far from the expected target, namely related to learning media that is still conventional, so that it has an impact on geography learning outcomes, therefore new innovative and modern learning media are needed. The purpose of this study was to determine the effect of using Google Earth learning media on the learning outcomes of students in class XI IPS 1 SMA Negeri Ngoro Jombang on natural disaster mitigation material in the 2022/2023 school year. This research is a quasi-experiment with data analysis using: descriptive analysis, normality test, homogeneity test, and Mann-Whitney and Wilcoxon tests. This research is a quasi-experiment with data analysis using: descriptive analysis, normality test, homogeneity test, and Mann-Whitney and Wilcoxon tests. The results showed that the learning outcomes of students at SMA Negeri Ngoro Jombang increased in the control class and experimental class with the calculation of the superior average of the experimental class.